Policy Analysis of West Papua Provincial Government Regarding Welfare Disparities of Migrants and Non-Migrants - Muh Miswar Bahri; Ahmad Munir; Sakaria Anwar (Universitas Muhammadiyah Gorontalo, 2021)
This study aimed to analyze the poverty factors of migrant and non-migrant households through socio-economic variables resulting from the West Papua Province government policy program. The research method used in this study was a quantitative research method using descriptive analysis depicted through diagrams. The data collection method used was secondary data collection derived from the results of the March 2020 National Socio-Economic Survey (SUSENAS) conducted by the Central Statistics Agency (BPS). The results of the study showed that the implementation of West Papua Province government policies had not succeeded in changing the poverty level of the population even though it has the authority as the organizer of special autonomy. Special treatment for non-migrant residents had not been able to eliminate the disparity in the level of welfare between the migrant population. The majority of poor households in West Papua were affected by the age of the head of the household above 60 years, the number of household members more than four people, no health complaints, the education of the head of the household who is mostly below high school, working in the informal sector, living in rural areas and are non-migrant households.